Knowledge of Nurses about Third Goal International Patients Safety Goal - Fathul Jannah (JURNAL PROTEKSI KESEHATAN, 2020)
One of the goals of patient safety (IPSG) is third goal, which focuses on the safetyof treatment, especially the high-alert medications. Medication errors are the thirdleading cause of death after heart disease and cancer. This incident can bedetrimental to the patient and can endanger patient safety which can be done byhealth workers, especially in giving drugs to patients. For this reason, it isnecessary to know how much the nurses knowledge about this matter. The studywas a descriptive study with a sample of nurses in the inpatient rooms of twohospitals in Pekanbaru. The results shows that 55% and 48% of respondentshave good knowledge of the third goal.